2009
DOI: 10.2202/1553-3840.1255
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Nociceptive and Anti-Inflammatory Activities of Extracts from the Stem Bark of Croton macrostachyus (Euphorbiaceae) in Mice and Rats

Abstract: The present study evaluates the anti-nociceptive and anti-inflammatory properties of the aqueous and methylene chloride/methanol (CH2Cl2 / CH3OH) extracts of the stem bark of Croton macrostachyus. The extracts administered orally at the doses of 150, 300 and 600 mg/kg were examined against pain induced by acetic acid, formalin and pressure and against inflammation induced by carragenan, histamine and formalin. Both extracts induced a significant dose-dependent (P < 0.001) reduction in the number of abdomina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…However, standard ascorbic acid has shown strong antioxidant activity than test samples. e phytochemical studies reported showed that stem bark of Croton macrostachyus constituted major secondary metabolites such as flavonoids, phenols, terpenoids, saponins, tannins, alkaloids, and steroids [19,20]. ese phytochemicals were reported to have an antioxidant activity in previous studies [33][34][35][36][37][38][39][40].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, standard ascorbic acid has shown strong antioxidant activity than test samples. e phytochemical studies reported showed that stem bark of Croton macrostachyus constituted major secondary metabolites such as flavonoids, phenols, terpenoids, saponins, tannins, alkaloids, and steroids [19,20]. ese phytochemicals were reported to have an antioxidant activity in previous studies [33][34][35][36][37][38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…e plant showed antibacterial [15], antidiarrheal [16], anticonvulsant [17], antidiabetic [14], and antihyperalgesic activity [18]. e phytochemical screening showed that the stem bark of Croton macrostachyus constituted the major secondary metabolites such as tannins, steroids, alkaloids, phenols, terpenoids, saponins, and flavonoids, which might be the reason for the plant widespread pharmacological activity [19,20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Croton macrostachyus (Hochst) pipe cleaner ex and Galinier, is a plant used in African folk medicine to treat different ailments, including pain and inflammation [ 7 , 8 ]. Indeed, previous studies have shown that aqueous and organic extracts from the stem bark of C. macrostachyus given orally, possess antinociceptive and anti-inflammatory activities in distinct acute animal models [ 9 ]. The present study aimed at providing additional insight about the antinociceptive effects of the methanol/methylene chloride extract of the stem bark of C. macrostachyus in different models of chronic inflammatory and neuropathic pain and to evaluate its preliminary mechanisms of action.…”
Section: Introductionmentioning
confidence: 99%
“…The plant showed antimicrobial activity against pathogens which are common contaminants of wound, such as Staphylococcus aureus and Pseudomonas aeruoginosa (Kalayou et al, 2012;Taye et al, 2011). The plant is also reported to have significant anti-inflammatory and analgesic activities in animal models (Kamanyi et al, 2009). Even though majority of the Ethiopian population uses traditional medicine, only limited studies were conducted on the traditional medicinal plants compared to the multicultural diversity and the diverse flora of the country (Tekalign et al, 2010).…”
Section: Introductionmentioning
confidence: 99%